Concentraçãeo plasmática de progesterona durante o ciclo estral de jumentas (equus asinus) com ovulaçõees simples e duplas - Conceiçãeo, J. C. [UNESP]; Neto, L. M. Freitas; Filho, C. R. Aguiar; Araújo, G. H M [UNESP]; Oliveira, J. V.; Bartolomeu, C. C.; Oba, Eunice [UNESP]; Meira, Cezinande de [UNESP] (My University, 2009)
Ten estrous cycles of seven Machador Brasileiro jennies located at Estaçãeo Experimental de Zootecnia - Colina - Sãeo Paulo were monitored and the plasmatic progesterone concentration determined by the radioimmunoassay method in solid phase, employing commercial kits (DPC). For progesterone concentration determination and CL diameter there were excluded the animals which presented diestrus ovulations. The corpora lutea formed from single ovulations or double ovulations presented a mean diameter of 26.2 ± 4.4 and 22.1 ± 2.7 mm, respectively, which represented 66.1% and 64.1% of the preovulatory follicle diameter. The presence of two CLs from double ovulations was not reflected by a significant increase on progesterone concentrations.
Plasma concentration of progesterone during the estrous cycle in jennies (equus asinus) with single and double ovulations
Keywords: Corpos lucteum; Equidae; Ovary; Animalia; Equus asinus